Strategic Planning Practices and Performance: The Story So Far in Parliamentary Service Commission in Kenya - Moses Mpisili Lemuna; Stephen Muathe (European Scientific Journal, ESJ, 2021)
The economic and political change in today’s organizations is the norm and the social and technological change is highly accelerating posing extremely complex task and uncertainty to those responsible for strategic planning. Therefore, in executing various decisions there is need for managers to achieve a total understanding of strategic planning prior to effectively implementing it. This study investigated the influence of strategic planning practices on the performance of Parliamentary Service Commission in Kenya. The study specifically examined influence of environmental scanning, objective setting, stakeholder involvement and communication on performance of Kenyan Parliamentary Service Commission. The study was anchored on resource-based view; dynamic capability; balance score card and institutional theories. Descriptive survey research design was used. The target population comprised of eight hundred and five respondents who are the permanent staff of the Parliamentary Service Commission. However, a sample size of eighty-one respondents was selected using simple random sampling. Data was obtained using questionnaires and analyzed through descriptive and inferential statistics specifically multiple regressions and correlation. The study established that environmental scanning, objective setting, stakeholder involvement and communication had a positive and significant effect on the performance of Parliamentary Service Commission in Kenya. The study recommends that the Commission should identify the persons to be involved in the environmental scanning, create a competent team of employees and assign them relevant responsibilities. The Commission needs to set objectives that can be defined in a quantifiable and measurable terms within its strategic plan beside establishing responsibility for ensuring the task is undertaken and for writing it up for the report on stakeholder engagement. The Commission should link communication to the strategic plan, including the organization’s mission, vision and values, its strategic goals and objectives.